Accessible tourism as an educational resource for the socialization of children with disabilities - Tatyana Nikolaevna Poddubnaya (Вестник Майкопского государственного технологического университета, 2023)
The key factors in the new economy are formation of an accessible environment for people with disabilities, including disabled children. This issue is one of the priorities of the states included in the world educational space and is considered as the realization of the constitutional rights of citizens. This activity was initiated by a number of international and domestic documents. In our country the formation of an accessible environment is carried out in the aspect of the implementation of the State Program of the Russian Federation «Accessibility», which provides for the creation of a barrier-free environment for the effective integration of citizens with disabilities into society. This initiates pedagogical research devoted to the study of the educational opportunities of accessible tourism for the full integration of children with disabilities in society. This circumstance confirms the relevance of our research and allowed us to formulate the research problem, which is to identify the possibilities of accessible tourism as an educational resource for the socialization of children with disabilities.The purpose of the research is to substantiate the possibilities of accessible tourism as an educational resource for the socialization of children with disabilities. To achieve this goal, the following research methods were used: the study of scientific literature and information from Internet sources, analysis, generalization, description.The results of the research are as follows the role of cultural and educational tourism as an effective tool for the social rehabilitation of minors with disabilities in a specially organized accessibleenvironment has been revealed. Using the example of barrier-free inclusive tourism, the experience of using the accessible environment as an educational resource for the socialization of children with disabilities has been described.Key conclusions are: cultural and educational tourism has an impact on the education of the personality of a disabled child, developing, first of all, his emotional and value attitude to cultural heritage and creating conditions for the spiritual sublimation of his needs, which can often not be satisfied in real life; the creation of a barrier-free environment in relation to tourism activities includes augmented reality technologies (mobile applications for museums, virtual tours, tours in sign language, tactile maps, etc.). The conclusion is drawn that the development of accessible tourism is a powerful factor in the socialization of children with disabilities in a new educational environment.